Matthew's account of the massacre of the innocents in light of its reception history - Cho, Sung J. (Scriptural traces: critical perspectives on the reception and influence of the Bible, 2021)
Cover -- Series -- Title -- Copyright -- Contents -- Figures -- Acknowledgments -- Abbreviations -- 1 Matthew and Reception History -- 2 A Close Reading of Matthew 2:16-18 -- 3 Massacre of the Innocents in Early Patristic Tradition (Second to Fifth Century) -- 4 Massacre of the Innocents from Sixth Century to 1516 -- 5 Massacre of the Innocents from 1517 -- 6 Visual Interpretations of the Massacre of the Innocents -- 7 Concluding Reflections -- Appendix A: Massacre of the Innocents in Modern Commentaries -- Appendix B: The Massacre of the Innocents in Commentaries from 1517 through the Nineteenth Century -- Appendix C: Massacre of the Innocents in Art -- Select Bibliography -- General Index -- Scripture Index.